Assessing the physical potential capacity of direct air capture with integrated supply of low‐carbon energy sources. Issue 1 (8th December 2021) - Fahr, Steffen; Powell, Julian; Favero, Alice; Giarrusso, Anthony J.; Lively, Ryan P.; Realff, Matthew J.
Abstract: Direct Air Capture (DAC) is a negative emission technology that can remove up to 10–20 Gt of CO2 per year. However, to achieve this potential, DAC systems must be coupled to suitable locally available energy sources and sited near geological storage. This study explores the potential of low‐carbon energy sources to supply power and heat to the DAC process in a dedicated, self‐sufficient system tailored for each energy source. Solar, geothermal, woody biomass, wind, and nuclear energy sources are assessed for their global energy supply potential and possible land use requirements. While the options differ in area requirement and regional efficacy, we estimate that all the regionally specific technologies considered can supply energy to achieve significant removal of carbon dioxide from the atmosphere globally. The amount of energy physically available from solar, offshore wind, and woody biomass converts to a removal potential of 160–971, 45–150, and 2–5 Gt CO2 /year, respectively. Thus, negative emission targets can be reached by utilizing a moderate fraction of the overall potential of several different low‐carbon energy sources for DAC while the magnitude of the potential changes significantly according to the source of energy. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.